2019
DOI: 10.1016/j.jtho.2018.10.161
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Crizotinib in Resectable Locally Advanced Non–Small Cell Lung Cancer with ALK Rearrangement

Abstract: Background: Locally advanced NSCLC is one of the most heterogeneous conditions, with multidimensional treatments involved. Neoadjuvant therapy had been commonly considered an optimal management strategy for patients with operable locally advanced. However, as targeted therapy has been widely applied in advanced NSCLC, neoadjuvant targeted therapy has remained poorly explored in locally advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 15 publications
(13 reference statements)
2
71
1
Order By: Relevance
“…Second, for patients with locally advanced lung cancer and N2 positive status, which is highly heterogeneous, neoadjuvant-targeted therapy has been proven safe and effective in patients harboring activating mutations in oncogenes such as EGFR and ALK. 14,15 Multiple ongoing clinical trials incorporating checkpoint inhibitors into neoadjuvant therapy for NSCLC have revealed encouraging findings of high response rates in major pathologic characteristics. [16][17][18] Therefore, neoadjuvant-targeted therapy or immunotherapy is an option to be considered when medical supply is limited and immediate operation is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Second, for patients with locally advanced lung cancer and N2 positive status, which is highly heterogeneous, neoadjuvant-targeted therapy has been proven safe and effective in patients harboring activating mutations in oncogenes such as EGFR and ALK. 14,15 Multiple ongoing clinical trials incorporating checkpoint inhibitors into neoadjuvant therapy for NSCLC have revealed encouraging findings of high response rates in major pathologic characteristics. [16][17][18] Therefore, neoadjuvant-targeted therapy or immunotherapy is an option to be considered when medical supply is limited and immediate operation is not available.…”
Section: Discussionmentioning
confidence: 99%
“…In the April 2019 issue of the Journal of Thoracic Oncology, we reported cases of ALK-positive locally advanced NSCLC from two institutions in which neoadjuvant crizotinib showed quite acceptable efficacy and tolerability. 1 Herein, we further describe the pathological evaluation and dynamic detection of circulating tumor DNA (ctDNA) in one patient receiving neoadjuvant crizotinib. Figure 1 summarizes the details of the entire therapeutic process.…”
mentioning
confidence: 99%
“…To the Editor: BRAF V600E mutation accounts for approximately 1.5% of lung adenocarcinoma. 1 Clinical studies have proven positive antitumor effect of dabrafenib, a BRAF inhibitor, plus trametinib, an MEK inhibitor, in BRAF V600Emutated NSCLC patients. 2,3 BRAF V600E mutation serves as one of the resistance mechanisms to osimertinib.…”
mentioning
confidence: 99%
“…-Hippocrates of Kos (c.460-370 BC) 1 The case series report referencing crizotinib in a neoadjuvant setting for the locally advanced NSCLC of Zhang et al 2 unveils far more questions regarding preoperative targeted therapy in comparison to its ability in answering existing dilemmas. Hippocrates' triad of drugs, surgery, and radiotherapy covers the entire armamentarium of oncopulmonology.…”
mentioning
confidence: 99%
“…We have no other choice but to properly portray our role in the assigned scene while we are "waiting for Godot." Zhan et al 2 made their bit.…”
mentioning
confidence: 99%